Cluster initiatives as a chance for the development of the furniture industry in Poland in the conditions of a crisis: The example of the Swarzędz Cluster of Furniture Producers - Dyba, Wojciech M.; Stryjakiewicz, Tadeusz (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2014)
The main aim of this article is to present cluster initiatives as a chance for the development of small and medium-sized enterprises operating in the furniture industry in Poland (especially under crisis conditions). It is an important branch of the national economy, generating ca. 2% of the GDP and accounting for ca. 6% of Polish exports. Firstly, the state of the Polish furniture industry in 2013 is presented. The conditions and prospects of its development are analyzed using Porter’s five forces concept. In the next part, the idea of cluster initiatives as a form of co-operation between competing enterprises is described and illustrated with the use of some examples from Poland as a whole. The paper ends with a case study of Swarzędz - a city of carpenters and furniture producers. This industry has a long tradition in Swarzędz and is sustained to the present day. Currently, the Swarzędz Cluster of 182 Wojciech M. Dyba, Tadeusz Stryjakiewicz Furniture Producers is being formed with the initiative from the local Guild of Swarzędz Carpenters. Additionally, its development strategy is being established and is to be funded from the Innovative Economy Operational Programme.